Always the Ideal? Exploring the Risks of Refugee Participation in Research - Lokot, Michelle; Hashmi, Iram; Hartman, Erin; Zreik, Thurayya; Wake, Caitlin (Refuge: Canada’s Journal on Refugees, 2024)
Researchers in humanitarian settings increasingly encourage refugees and internally displaced persons (IDPs) to participate within broader research processes, beyond solely providing data. However, efforts to increase participation in research may be tokenistic, complicated by the challenges present in humanitarian settings. The assumption that more participation is always good has meant sometimes limited reflection occurs on the challenges associated with such participation. This study explores the possibilities and realities for refugee and IDP participation in research based on interviews with practitioners and academics who conduct participatory research with refugees and IDPs. It discusses lack of consensus in defining participation and explores five risks of participation that challenge the assumption that participation is always desirable and appropriate.